Modern Monetary Theory (MMT): An Evaluation of its Premises and its Political Consequences - Mueller, Antony Peter; Vaz-Curado, Samuel Fernandes Lucena (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The Modern Monetary Theory (MMT) has gained center stage of economic debate with proposals for major social and environmental welfare projects in the United States. This article aims to present the basic assumptions of MMT and its position in economic theory. The roots of MMT are associated with the neo-Marxist economist Michal Kalecki, who asserts that deficits do not matter. The adherents of MMT argue that projects such as Medicare for All, Green New Deal, and job security face no major fiscal restraint. For the government as the sovereign creator of the national currency as a legal tender, budget deficits do not matter because it can always create as much money as is necessary to finance its expenditures. The paper discusses the main policy proposals of Modern Monetary Theory and elaborates the critique and limitations of its agenda.